(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The main purpose of the article is to clarify the category of the «financial potential of an enterprise» on the basis of the generalization of existing research approaches and to formulate the conceptual foundations for its further research as an object of strategic analysis. The above mentioned purpose is detailed in such objectives: 1) to provide critical evaluation of existing research approaches to the concept of financial potential; 2) to highlight the general shortcomings of the approaches presented and clarify the interpretation of financial potential category; 3) to propose a conceptual framework for research of the financial potential of an enterprise as an object of strategic analysis. A critical assessment of the existing definitions of the category led to conclusion that in most cases the interpretation of the financial potential is focused on the internal potential of the enterprise, that reflects the material content of this concept (or resource approach). In the definitions the main focus is on the ultimate goal of utilization of the financial potential (obtaining the maximum financial result, maximum competitive advantages, targeted financial development, etc. (an effect approach)). The structure of the financial potential is often neglected in description of its content; due attention is not paid to the subjective component of the category, etc. In the article, in accordance with the objectives set, the following research methods were used: analysis, synthesis and comparison – for the composition of the research object; the logical generalization and scientific abstraction – for the clarification of the categorical apparatus. The object of the research is the financial potential of an enterprise; the subject is the theoretical foundations for the study of the financial potential as an object of strategic analysis. The applied value of the research results is in the potential possibility for the development of new methodological approaches to the formulation, structuring and strategic analysis of the financial potential of an enterprise. The article substantiates that the financial potential is a complex category identified by the author as a set of financial opportunities for the development of an enterprise, due to the availability of sufficient financial resources and an effective financial management system aimed at achieving the company’s strategic financial position in the external environment. The specified definition of financial potential can be applied both in the past time period (as the availability of resources and management systems), in the current period (as a set of financial opportunities) and in the future (as achievement of the company’s strategic financial position in the external environment). With respect to this the author defines the conceptual foundations for study of the financial potential of an enterprise based on a combination of resource concept, cybernetic and systemic approach, development theory, theory of self-organization and the concept of dynamic abilities. This allowed to deepen the understanding of the concept and direct the attention of researchers to the improvement of methodological provisions for strategic analysis of the financial potential of an enterprise.